A checkpoint to pain - Hirth, Michael; Gandla, Jagadeesh; Kuner, Rohini (Nature neuroscience, 2017)
The checkpoint pathway consisting of programmed death ligand 1 (PD-L1) and its receptor, PD-1, modulates immune function in cancer and infection, but unexpectedly, it also silences pain signals in nerves.
Gesehen am 12.07.2018